Revisão integrativa sobre as características epidemiológicas das infecções urinárias causadas por Escherichia coli de origem comunitária - Nogueira, Daniela Samara (2015)
Urinary infections of Community origin, caused by Escherichia coli, is a public health problem, they may be associated with infection caused by E. coli multidrug resistant.The objective of this study was to describe the prevalence and susceptibility profile of Escherichia coli in the urinary tract infection of community origin and to identify the scientific literature on the topic. A study of integrative literature review was conducted, within a timeframe of five years, including the publications between 2009 to 2014, about urinary tract infection of community origin. A total of 1319 publications was found, of these thirty six fulfilled the eligibility criterion. Urinary tract infections affect people worldwide and the Escherichia coli represents the main microorganism isolated. The empirical treatment happens in large proportions and the E. coli showed an increase in the rate of resistance to most antibiotics tested in the studies, is also worrying the spread of betalactamases-producing strains of broad spectrum. In some regions of Brazil, the antibiotics such as ampicillin, sulfamethoxazole/trimethoprim, norfloxacin, cephalothin and nalidixic acid should be avoided, whereas nitrofurantoin and cefuroxime can still be used safely.